Horn size is linked to Sertoli cell efficiency and sperm size homogeneity during sexual development in common eland (Taurotragus oryx) - Pintus, Eliana; Kotrba, Radim; Ros-Santaella, José Luis (Frontiers in Cell and Developmental Biology, 2024)
Background: In polygynous species, the development of secondary sexual characters is usually decisive for male reproductive success. However, our understanding about the links between the growth of these traits and reproductive efficiency is still elusive. Most research efforts in this topic have been also focused on adult males, although the development of some secondary sexual characters, like bovid horns, typically starts after birth, continues during the puberty and in some species, such as the common eland, slows or even stops during adulthood. In this study, we investigated the relationships between horn size and testicular function during sexual development in common elands using a comprehensive approach that considers both spermatogenic and sperm parameters. Methods: Twenty-two non-sexually mature common elands were used for the present study. Horn size, body mass, testes mass, and gonadosomatic index were assessed. Spermatogenic activity was determined by cytological and histological analyses. Sperm concentration, morphology, morphometry, and intramale variation in sperm size were evaluated on epididymal sperm samples. Cluster analysis was performed to explore the influence of age on relationships between horn size and reproductive function. Results: We found that bigger horns are associated with increased Sertoli cell efficiency and reduced intramale variation in sperm size. Both parameters were not related to one another while they have shown to be associated with enhanced sperm quality in ungulates. Moreover, horn size was positively linked to the testis mass, sperm concentration, and testicular investment in the seminiferous epithelium. Spiral length and basal circumference were the horn traits most strongly correlated with spermatogenic and sperm parameters as well as those responsible for the sexual dimorphism in this species. Cluster analysis rendered two groups: the first one including males ≤30 months old, while the second one those >30 months old. Horn development and reproductive function were still correlated within age groups, with the strongest relationship found between horn size and sperm size homogeneity in males >30 months old. Conclusion: Taken together, our results indicate that horn size can be regarded as a good index of male reproductive potential during sexual development and provide insights into the role of secondary sexual characters in sexual selection dynamics.